Characterizing the molecular weight distribution of dissolved organic matter by measuring the contents of electron-donating moieties, UV absorbance, and fluorescence intensity. (April 2020) - Wu, Qian-Yuan; Zhou, Tian-Hui; Du, Ye; Ye, Bei; Wang, Wen-Long; Hu, Hong-Ying
Highlights: Molecular weight (MW) distribution of electron-donating moiety (EDM) was evaluated. MW fraction of 1.8–6.9 k Da accounted the majority of EDM in natural DOM. MW fraction of <1 k Da accounted the majority of EDM in DOM of wastewater effluent. The heterogeneous MW distribution of EDM in DOM is related to that of UVA254. Relative decreases of EDM and UVA indicated the oxidation pathways for MW fractions. Abstract: Electron-donating moieties (EDM) have recently been used to characterize the redox properties and treatability of dissolved organic matter during water and wastewater treatment. In this study, size exclusion chromatography followed by a derivatization-spectrometric method was developed to determine the molecular weight (MW) distribution of EDM in dissolved organic matter. The relationships between EDM concentration and chromophore content (indicated by UVA254 ), fluorophore content (indicated by fluorescence), and dissolved organic carbon (DOC) concentration were analyzed for different MW fractions. In general, natural organic matter (NOM) showed higher total EDM concentration and higher EDM average MW than effluent organic matter (EfOM). For NOM, fractions with MW between 1.8 k and 6.9 k Da accounted for most of the EDM (45.4%–48.6%), followed by the fractions with MW < 1.8 k Da (25.6%–42.4%). By contrast, the EDM in EfOM occurred predominantly in fractions with MW < 1 k Da (51.8%–58.6%), with lower concentrations in fractions with MW > 1.8 k Da (<20.2%). The heterogeneous MW distribution of EDM was strongly correlated to the presence of chromophores, but not DOC or fluorophores. The EDM difference between MW fractions suggested that the fraction with MW 1.8–6.9 k Da (40.7%–47.1%) and the fractions with MW < 1 k Da (50.2%–58.8%) should be the dominant oxidant consumers in NOM and EfOM, respectively. When the EDM was normalized by the DOC for each MW fraction (EDMMW /DOCMW ), the EDMMW /DOCMW of relatively high-MW fractions (>1.8 k Da) is 1.2–1.9 times of relatively low-MW (<1 k Da) fractions for both NOM and EfOM, which indicates that higher-MW fractions are more susceptible to chemical oxidations. The relationship between EDM change and UVA254 change varied for different MW fractions during advanced ozonation treatment, because of the different oxidation mechanisms in operation for MW fractions. The ozonation of EfOM fractions with higher MW (>1.8 k Da) and lower MW (<1 k Da) preferentially resulted in benzoquinone formation and ring-cleavage, respectively.